Is more really more? Evidence of a curvilinear relationship between the extent of telework and employees’ temporal alignment of work and private life in Germany - Mergener, Alexandra [Verfasser]; Rinke, Timothy [Verfasser]; Ines Entgelmeier [Verfasser] (My University, 2024)
„Studies exploring not only whether, but also to what extent, telework can improve employees’ ability to coordinate private and work-related demands are largely absent. Using a probability-based large-scale survey of employees in Germany (N = 14,999), this study provides evidence of an inverted U-shaped relationship between the extent of telework and employees’ temporal alignment of work and private life, i.e., their success in considering personal and family matters when scheduling work. When telework comprised up to 40 percent of the total working time, employees were observed to temporally align their work and private life better than those who only worked on-site. Additional analyses indicated that particularly men, and even more so fathers, experience improved work and private life alignment with frequent teleworking. For women with and without children, however, highly extensive teleworking not only loses its positive effect, but is associated with less success in aligning work and private life compared to non-teleworking. To be able to benefit from telework, even when it is used extensively, clear rules are needed, for example, regarding expectations of accessibility for paid work as well as for home and care work.“ (authors' abstract; BIBB-Doku)
Keywords: G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.3.3 Arbeitsformen, Techniken; G 2.4.2 Lebenskonzepte, -stile, Werte; 370; 300; Arbeitszeitgestaltung; Telearbeit; Work-Life-Balance; Beruf und Familie; Einflussfaktor; Befragung